Prevalence of Seed-Borne Fungi on Soybean (Glycine max L. Merr.) Seeds Stored Under Medium-Term Cold Room Facilities: Implications for Genebanks - Abdul J Shango; Sognigbé N’Danikou; Shebati Ramadhani; Saphina Sumaye; Jonas Nickas; Michael L Daud (Seeds)
This study examined the prevalence of seed-borne fungi in polyethylene plastic-packaged soybean seeds stored in a genebank and identified factors influencing their incidence. Twenty-four seed lots were sampled from the collection stored at 10 °C in the World Vegetable Center genebank in Arusha, Tanzania. The seeds used were those regenerated and harvested in 2015, 2016, and 2017. A seed health test was conducted for sterilized seeds on potato dextrose agar, sterilized seeds on top of the paper, and unsterilized seeds on top of the paper. Seven-year-old sterilized seeds plated on top of the paper exhibited the highest germination percentage (74 ± 7.09%) and lowest fungal incidence (7.00 ± 4.41%). Conversely, seven-year-old unsterilized seeds plated on top of the paper had the lowest germination (22.00 ± 6.97%) and highest fungal incidence (79.00 ± 8.31%). Older seed lots showed significantly higher equilibrium seed moisture content (Eqmc), though seed age had no significant influence on germination percentage or fungal incidence. Seed germination percentage showed a significant negative relationship with Eqmc, though Eqmc had no significant effect on fungal incidence. Meanwhile, germination percentage showed a significant negative relationship with fungal incidence. Six fungi isolates were identified using their morphological features from soybean seed samples: Absidia glauca, Aspergillus niger, Fusarium spp., Mucor hiemalis, Pestalotiopsis versicolor, and Sordaria macrospora. It is concluded that high fungal incidence negatively affects seed germination but is not significantly correlated with seed moisture content. The dry and cold storage conditions in the genebank, while effective in extending seed longevity, can unintentionally allow seed-borne mycoflora to persist. Although fungi may not actively proliferate under these conditions, they may do so when favorable conditions are restored, such as during germination tests, and consequently may compromise seed viability. Therefore, this study emphasizes the importance of increased systematic seed health checks before storage in genebanks to ensure optimal seed quality, and the replacement of all polyethylene plastic bags to aluminium foil packaging.